Abundance of Cottus poecilopus is influenced by O2 saturation, food density and Salmo trutta in three tributaries of the Rožnovská Bečva River, Czech Republic. Issue 2 (31st December 2014) - Baran, R.; Kubecka, J.; Kubín, M.; Lojkásek, B.; Mrkvička, T.; Ricard, D.; Rulík, M.
<x xml:space="preserve">Abstract</x> The distribution patterns of alpine bullhead Cottus poecilopus in three tributary streams of the Rožnovská Bečva River (Danube basin) were studied with respect to temperature, oxygen concentration and saturation, shading, current, conductivity, total organic carbon (TOC), nitrates and phosphates, biochemical oxygen demand (BOD5), pH, redox potential, bottom grain structure, density of macroinvertebrates and the abundance of brown trout Salmo trutta. Sites with lower abundance per hectare of C. poecilopus differed significantly in dissolved oxygen saturation, density of macroinvertebrates during the autumn period (positive correlation with C. poecilopus) and in abundance per hectare of S. trutta (negative correlation). These results indicate that these factors significantly influence the distribution of this endangered species in the studied catchment and that stocking of S. trutta will impair its recovery.